La retòrica i la lingüística, 1775-1900 - Solà, Joan (Caplletra. Revista Internacional de Filologia, 2015)
It is a well known fact that school manuals' of the 18th and 19th centuries centred on the teaching of Rhetoric are closely linked with those geared towards the study of language in general and of Grammar in particular. The article, based on the work by Marcet-Solà, shows the relevance of this especial relationship and offers illustrative material from these manuals, restricted, like the work referred to, to the Catalan speaking area.